2019
DOI: 10.3201/eid2509.180747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumococcal Conjugate Vaccines on Pneumococcal Meningitis, England and Wales, July 1, 2000–June 30, 2016

Abstract: We describe the effects of the 7-valent (PCV7) and 13-valent (PCV13) pneumococcal conjugate vaccines on pneumococcal meningitis in England and Wales during July 1, 2000–June 30, 2016. Overall, 84,473 laboratory-confirmed invasive pneumococcal disease cases, including 4,160 (4.9%) cases with meningitis, occurred. PCV7 implementation in 2006 did not lower overall pneumococcal meningitis incidence because of replacement with non–PCV7-type meningitis incidence. Replacement with PCV13 in 2010, however, led to a 48%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
5
39
1
Order By: Relevance
“…They also reported that children with underlying chronic conditions were more prone to develop IPD from non‐PCV13 serotypes 21 . A surprising finding in our data—no change in hospitalisation rate for pneumococcal meningitis post‐PCV13—could also be related to serotype conversion, as in a British study which found no change in pneumococcal meningitis incidence after PCV7, with decrease only after PCV13 was introduced 22 …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…They also reported that children with underlying chronic conditions were more prone to develop IPD from non‐PCV13 serotypes 21 . A surprising finding in our data—no change in hospitalisation rate for pneumococcal meningitis post‐PCV13—could also be related to serotype conversion, as in a British study which found no change in pneumococcal meningitis incidence after PCV7, with decrease only after PCV13 was introduced 22 …”
Section: Discussionsupporting
confidence: 65%
“…21 A surprising finding in our data-no change in hospitalisation rate for pneumococcal meningitis post-PCV13-could also be related to serotype conversion, as in a British study which found no change in pneumococcal meningitis incidence after PCV7, with decrease only after PCV13 was introduced. 22 Another possible explanation for the rise in IPD hospitalisations may be a trend towards admission rather than outpatient care. Tam et al reported that even with a reduction in the overall IPD diagnoses in the post-PCV13 period, an increased proportion of patients with IPD were hospitalised for their care.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
“…Specifically, the vaccine serotypes 1, 6A/B, 19A, and 23F were not identified by the end of the surveillance period. Similar trends in VST pneumococcal meningitis reduction have been reported previously in some Sub-Saharan African countries and elsewhere [10,12,[24][25][26][27][28][29][30]. In The Gambia, PCV13 implementation in 2011 (following the switch from PCV7) resulted in reductions in invasive pneumococcal diseases [31].…”
Section: Plos Onesupporting
confidence: 75%
“…reported [29,32]. Part of the shift also may be due to replacement of VSTs by NVSTs due to PCV13 effectiveness, a phenomenon which has been documented globally [27,28,33].…”
Section: Plos Onementioning
confidence: 94%
“…Immunization of children is effective for disease prevention worldwide. From 2000 to 2015 in particular, the frequency and mortality rates of meningitis due to S. pneumoniae and type B H. influenzae were reduced following the active implementation of conjugate vaccines worldwide [23,24]. In addition, in Japan, which shares climate and infectious disease characteristics with Korea, a recent study has shown that the frequency of bacterial meningitis has been decreasing since the last several years owing to increased vaccinations against H. influenzae and S. pneumoniae [25].…”
Section: Discussionmentioning
confidence: 99%